Ag doping effect on electronic and thermoelectric properties of SrTiO3 (0 0 1) surface - Azevedo, Sérgio A. [UNESP] (2023)
The search for sustainable energy sources has been a global demand in recent decades. In this context, thermoelectric materials (TE) have been an interesting alternative for this purpose and constitute a relevant research topic for increasing the efficiency of sustainable energy production. In this sense, computational simulation of the functionalization of SrTiO3 is proposed via Ag-doping on the (0 0 1) surface. The results show the emergence of a midgap trap state, leading to a band gap energy decrease, an increase in dielectric constants and the effective mass electron. The Ag-doping generates a decrease in electrical conductivity and an increase in the figure of merit, which are associated with a significant reduction in thermal conductivity (∼5 times), indicating that the material can be used with TE at high temperatures. The Ag-SrTiO3 (0 0 1) surface is promising for developing new thermoelectric devices.